2017
DOI: 10.4236/aim.2017.74020
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of <i>Helicobacter pylori</i> and Eradication Rate in Japanese Pediatric Patients

Abstract: Helicobacter pylori (H. pylori) eradication rates achieved with a proton pump inhibitor (PPI), amoxicillin and clarithromycin have recently decreased to about 75% because of the increase in clarithromycin resistance in Japan. In the present study, H. pylori resistance rates against clarithromycin, amoxicillin and metronidazole were investigated in pediatric patients and eradication rates were evaluated when tailored antibiotics regimens based on antibiotic sensitivity data were used. We isolated H. pylori endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…et al, in Portugal, and Butenko T. et al, in Slovenia, during the period 2013–2017, which considered eradication treatment based on antibiotic sensitivity for 14 days, the percentage of eradication was 97.8% and 85.9%, respectively [ 7 , 13 ]. In Asia, this figure in Ikuse’s study (2016) on Japanese children was 93.8% [ 6 ]. According to a pilot study by Zhang Y.D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…et al, in Portugal, and Butenko T. et al, in Slovenia, during the period 2013–2017, which considered eradication treatment based on antibiotic sensitivity for 14 days, the percentage of eradication was 97.8% and 85.9%, respectively [ 7 , 13 ]. In Asia, this figure in Ikuse’s study (2016) on Japanese children was 93.8% [ 6 ]. According to a pilot study by Zhang Y.D.…”
Section: Discussionmentioning
confidence: 99%
“…Further benefits mentioned are the reduction in costs and risks of salvage therapy and, ultimately, the prevention of and reduction in gastric cancer incidence [ 4 , 5 ]. Several researchers worldwide have documented that antibiotic-susceptibility-based eradication of H. pylori in children is highly effective [ 6 , 7 , 8 ]. Furthermore, recent reports on the antibiotic resistance of H. pylori bacteria in Vietnam showed that a very high percentage of H. pylori is resistant to commonly used antibiotics, and the recommended eradication treatment is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…và cộng sự ở Bồ Đào Nha (2017), điều trị tiệt trừ theo sự nhạy cảm kháng sinh trong 14 ngày, tỷ lệ tiệt trừ đạt 97,8% [11]. Ở Châu Á, nghiên cứu của Ikuse T. và cộng sự ở Nhật Bản (2016) là 93,8% [5]. Có nhiều yếu tố có thể liên quan đến tỷ lệ tiệt trừ thấp trong nghiên cứu của chúng tôi.…”
Section: Bàn Luậnunclassified